The Criminal Code of Mongolia. The General Part. Punishment - V. M. Stepashin (Правоприменение)
The subject. The Criminal Code of Mongolia, as one of the newest criminal laws, needs to be studied.The purpose of the study is to identify the features of criminal punishment and its appointment in Mongolia.The author uses method of formal legal interpretation of Mongolian Criminal Code. Main results: (1) Criminal liability in Mongolia consists of punishments and coercive measures. Its goals include: punishment, restoration of rights violated by a crime, and compensation for damage or prevention of new crimes, as well as re-socialization. (2) The system  of  punishments  has  been  significantly  simplified.  It  is  free  from  special punishments for military personnel, as well as types of punishment that duplicate each other in terms of content. There are 5 types of punishments in the current Criminal Code. Four of them can be assigned as the main ones: a fine, community service, restriction of movement rights, and imprisonment. The death penalty is excluded. The only additional type of punishment is deprivation of the right. The Court has been given a fairly wide margin  of  appreciation.  (3)  The  procedure  and  grounds  for  bringing  to  criminal responsibility and exemption from criminal liability. The Law establishes general rules for criminal prosecution and special rules for sentencing. The latter also provide for the possibility of release from punishment, as well as the application of coercive measures (suspended sentence or restriction of rights) to the perpetrator. Mitigation of punishment is achieved by setting a reduction coefficient applied not only to the upper, but also to the lower limit of the sanction. The imposition of punishment for multiple crimes allows for the addition of a fine with other types of punishment. The possibility of imposing imprisonment for a term exceeding twenty years is excluded. (4) Probation and compulsory measures. A suspended sentence of up to five years is an alternative to punishment as an independent compulsory measure, without imposing a custodial sentence. At the same time, the scope of application of probation is significantly narrowed. The court may attach all types of coercive measures to the prescribed punishment. (5) The specifics of sentencing minors under criminal law demonstrate the most vivid embodiment of the idea of humanizing the criminal policy of the state. The legislator ruled out the possibility of imposing a fine on minors, and transformed the punishment in the form of imprisonment into its sparing form - imprisonment in a special educational institution. 6. Liability of legal entities. The only form of punishment is a fine. Compulsory measures may be attached to it.Conclusions. It is necessary to use the positive experience of Mongolian legislation in addressing issues of punishment and its appointment in Russia.